MAPPING EFFORTS TO ENHANCE ELEMENTARY SCHOOL STUDENTS' LEARNING MOTIVATION IN SORONG REGENCY - Haryo Franky Souisa; Natalya Tutuarima (LPPM Politeknik Saint Paul Sorong, 2026)
This study aims to map efforts to enhance elementary school students' learning motivation in Sorong Regency through a systematic literature review of 43 journal articles published between 2014 and 2025. The method involves analyzing research trends based on geographic distribution, grade levels, and subject areas, as well as identifying gaps in educational interventions. The findings indicate that innovative teaching methods, interactive media utilization, and gamification are the most dominant strategies in increasing student motivation. However, research has primarily focused on upper-grade students (grades IV-VI) and subjects like science and mathematics, while lower-grade students and non-core subjects receive less attention. The conclusions emphasize the need for more contextual interventions, increased parental involvement, and the integration of educational technology to ensure equitable learning motivation. These findings offer recommendations for educators and policymakers in designing more inclusive and effective educational strategies for elementary school students in Sorong Regency.